2020
DOI: 10.1016/j.exis.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Democracy in emerging markets: A new perspective on the natural resources curse

Abstract: Using annual data from 1980 to 2014, we reexamine the relationship between democracy and natural resources for a large sample of emerging market economies. Controlling for human capital (or real GDP per capita) and openness measures, dynamic panel methods address endogeneity from more democratic regimes demanding better control of rents. We find that democracy responds positively to natural resource rents in GDP (NAT) and negatively to terms of trade (TOT). The NAT positive effects mitigate the negative impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Understandably, the economy looms large in any discussion of democratic trends in emerging countries, with claims that economic resources increasingly drive accountability and decision‐making participation (e.g., Mollick et al., 2020). Even in terms of foreign policies, such countries may be described as ‘emerging‐market’ democracies (Brookings Institution, 2011).…”
Section: Emerging Countries and Democracymentioning
confidence: 99%
“…Understandably, the economy looms large in any discussion of democratic trends in emerging countries, with claims that economic resources increasingly drive accountability and decision‐making participation (e.g., Mollick et al., 2020). Even in terms of foreign policies, such countries may be described as ‘emerging‐market’ democracies (Brookings Institution, 2011).…”
Section: Emerging Countries and Democracymentioning
confidence: 99%
“…Using the quantile regression technique and data from 19 emerging countries covering the 1997-2010 period, Lv (2018) showed that above a certain income level, democracy contributes strongly to reduce CO 2 emissions. Similarly, Mollicka et al (2020) detected a positive relationship between democracy and natural resources rents. They also provided evidence that an increase in natural resources requires a participative decision-making process.…”
Section: Introductionmentioning
confidence: 91%
“…The 'resource curse' hypothesis indicates that countries with an abundance of natural resources (e.g.,petroleum) tend to have less economic growth, less democracy and lower institutional quality than countries with fewer natural resources (Mollick et al, 2020;Gilberthorpe and Papyrakis, 2015;Boutilier, 2017;Manzano and Gutiérrez, 2019;Ross, 2019;Moisé, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, there is an expectation that there will be a difference in government expenditure that is responding to changing oil revenues within different institutional frameworks. If oil resources are owned by the government, the government structure is a factor that is affecting the allocation and spending of oil wealth, as well as the resources of rent distribution (Mollick et al, 2020;Aslaksen, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%